CEGAH RESIKO TINGGI PADA IBU HAMIL DENGAN PENA SUASI (PENDAMPINGAN KELUARGA DAN SUAMI SIAGA) - NUR Chabibah; Ratna Arifiana; Laela Nisya Ayuanda (Jurnal Batikmu, 2021)
Maternal and infant mortality rates in Indonesia are still quite high and far from the targets of the RPJMN and SDGs. One of the causes of maternal death is high-risk pregnancy. Efforts can be made to reduce high-risk pregnancies with programs involving husbands and families. The Community Service Program carried out by the UMPP team of lecturers and students in collaboration with the Kedungwuni II Health Center is to prevent high risk in pregnant women with PENA SUASI (Families Assistance and Alert Husband). The methods used in this PKM are brain storming, couple games, lectures, question and answer discussions. Conducted one time with the number of participants 20 pregnant women with high risk and their companions, both husbands and families. the activity consists of four stages; namely the opening stage, the core stage, the discussion and question and answer stage, the closing stage. The results of the activity went smoothly and all pregnant women and their companions were enthusiastic to participate in the implementation of this community service activity. 100% of couples always accompany mothers for antenatal care, 75% of pregnant women and their partners have the same place of delivery planning and 80% of pregnant women and their partners plan exclusive breastfeeding. Conclusion It is hoped that the family assistance program and husband on standby will continue to be developed and increase participation from all components, both from midwives, health centers, and pregnant women, so that mothers during pregnancy and preparation for childbirth feel safe and comfortable because of the support they get and the welfare of the mother and fetus will increase.